Penundaan Pemilihan Umum di Negara Hukum: Kajian Demokrasi Konstitusional (General Elections Postponement in Rule of Law: A Study of Constitutional Democracy) - Ayon Diniyanto (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2022)
The issue of postponing the general election has become a public debate. This raises the question; can the postponement of the general election be realized in Indonesia? The question arises because the constitution does not regulate the postponement of the general election. This is a problem for Indonesia as a constitutional democracy and a state with the rule of law. The research problem in this study are: (1) what are the chances of postponing the general election in a state with the rule of law? (2) how does constitutional democracy view the postponement of the general election? and (3) what is the formulation of a constitutional and comprehensive postponement of the general election? This study uses doctrinal research with a legal approach, a concept approach, and a case approach. The results of the discussion state that the possibility of postponing the general election in a state with the rule of law can be held constitutionally and non-constitutionally. It is constitutionally carried out with constitutional amendments. Non-constitutionally, it is held by issuing decrees and establishing constitutional conventions. If the postponement of general elections is carried out in Indonesia at this time, it would be contrary to constitutional democracy. For this reason, it is necessary to formulate norms in the constitution which regulate the postponement of general elections and constitutional deadlocks. The conclusion of this study states that the possibility of postponing the general election in a state with the rule of law can be done by constitutional and non-constitutional means; postponement of general elections in Indonesia is contrary to constitutional democracy, and there is a need to have a formulation of norms that resolve the constitutional deadlock in the constitution. For this reason, the MPR is advised to amend the constitution in order to prevent constitutional deadlock. AbstrakIsu penundaan Pemilu menjadi perdebatan di ruang publik. Hal ini menimbulkan pertanyaan, apakah penundaan Pemilu dapat diwujudkan di Indonesia? Pertanyaan tersebut muncul karena konstitusi tidak mengatur penundaan Pemilu. Ini menjadi problem bagi Indonesia sebagai negara demokrasi konstitusional dan negara hukum. Oleh karena itu, rumusan masalah penelitian ini, yaitu: (1) bagaimana peluang terjadinya penundaan Pemilu di negara hukum?; (2) bagaimana penundaan Pemilu dalam kacamata demokrasi konstitusional?; dan (3) bagaimana formulasi penundaan Pemilu yang konstitusional dan komprehensif? Penelitian ini menggunakan jenis penelitian doktrinal, dengan pendekatan hukum, pendekatan konsep, dan pendekatan kasus. Hasil pembahasan menyatakan bahwa peluang penundaan Pemilu di negara hukum dapat dilakukan secara konstitusional dan non-konstitusional. Secara konstitusional dilakukan dengan amandemen konstitusi. Secara non-konstitusional dilakukan dengan mengeluarkan dekrit dan membangun konvensi ketatanegaraan. Jika penundaan Pemilu dilakukan di Indonesia saat ini, akan bertentangan dengan demokrasi konstitusional. Untuk itu, perlu ada formulasi norma dalam konstitusi yang mengatur mengenai penundaan Pemilu dan constitutional deadlock. Simpulan artikel ini menyatakan bahwa peluang penundaan Pemilu di negara hukum dapat dilakukan dengan cara konstitusional dan non-konstitusional; penundaan Pemilu di Indonesia bertentangan dengan demokrasi konstitusional; dan perlu ada formulasi norma yang menyelesaikan constitutional deadlock dalam konstitusi. Untuk itu, MPR disarankan melakukan amandemen konstitusi dalam rangka mencegah constitutional deadlock.